2011
DOI: 10.1002/jcp.22803
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a functional estrogen‐responsive enhancer element in the promoter 2 of PRDM2 gene in breast cancer cell lines

Abstract: The retinoblastoma protein-interacting zinc-finger (RIZ) gene, also known as PRDM2, encodes two protein products, RIZ1 and RIZ2, differing for the presence of a 202 aa domain, called PR domain, at the N-terminus of the RIZ1 molecule. While the histone H3 K9 methyltransferase activity of RIZ1 is associated with the negative control of cell proliferation, no information is currently available on either expression regulation of the RIZ2 form or on its biological activity. RIZ proteins act as ER co-activators and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…IGF-1 treatment increased expression levels of the RIZ forms lacking the PR domain in GC-1 cells. In conclusion, RIZ was still expressed in tumor phenotype and, according with previous results obtained in MCF-7 breast cancer cell line, E2 modifies the RIZ1/RIZ2 ratio, lowering the expression level of RIZ1 and raising the RIZ2 one [35,37]. E2 treatment also induces GC-1 [40] and TCam-2 proliferation (data not shown) [41] suggesting that the effect on cell growth is exerted by RIZ proteins.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…IGF-1 treatment increased expression levels of the RIZ forms lacking the PR domain in GC-1 cells. In conclusion, RIZ was still expressed in tumor phenotype and, according with previous results obtained in MCF-7 breast cancer cell line, E2 modifies the RIZ1/RIZ2 ratio, lowering the expression level of RIZ1 and raising the RIZ2 one [35,37]. E2 treatment also induces GC-1 [40] and TCam-2 proliferation (data not shown) [41] suggesting that the effect on cell growth is exerted by RIZ proteins.…”
Section: Resultssupporting
confidence: 74%
“…Electrophoresis and Western blot analysis were performed as described elsewhere [37] by using the rabbit polyclonal anti-RIZ antibodies (ab9710, Abcam Ltd., Cambridge, UK) or the rabbit polyclonal anti-ERα antibodies (Santa Cruz Biotechnology Inc., Santa Cruz, CA, USA). The same membrane was stripped and reprobed with the mouse monoclonal anti-α-tubulin antibody (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…sPRDM16 impedes the growth-inhibitory effect of TGF β on ATL cell lines [61]. estrogen responsive element (ERE) [64]. Consistently, the same group previously reported that in the breast cancer cell line MCF7, estrogen treatment shifted the expression balance of the two isoforms to favour the shorter one [41].…”
Section: Prdm15 Prdm16mentioning
confidence: 70%
“…The resulting critical mutations can trigger the development of breast and also other human malignancies [18,19]. Estrogens may further affect cell proliferation via several genomic and non-genomic pathways [20,21]. The mechanisms of genomic signaling of estrogens have been reported by several researchers [22,23,24,25,26] (shown in Figure 1A,B), whereas the non-genomic mechanisms are still not well understood (shown in Figure 1C,D).…”
Section: Introductionmentioning
confidence: 99%